(untitled) (Orfeu, 2021)
In approaching creative practices in teachers formation, the paper seeks to highlight a emergent aspect in the project Musical Education in teachers formation from Pedagogy Undergraduation courses in Rio Grande do Sul, Brazil: hearing and creation processes in noising experience (LINO, 2020a). The research’s quantitative and qualitative analysis highlight the reduced space for music teaching as a curricular discipline in Rio Grande do Sul’s universities and timid presence of creative practices in teacher’s musical repertoire. The strengthening of educational scenery comprise the teacher’s formation process beyond the mandatory character of curriculum guidelines. It demands to conceive music as everyday life potency offered and enlarged in the collective exercise of composing conversations (CAGE, 2015). Living the process of hearing and musical creation, from its ludicity, the experience of noising (LINO, 2008) inhabits pedagogy as a linguistic poetic gesture to highlight the composition of teaching. Creative practices burst teachers’ formation to inaugurate sense, to show the ludic, the sensitive, the singular and the insurmountable human dimension of music and score and sharing.